Gallring med vinkelkran : en jämförande studie av skördarkran med och utan horisontellt ledad vipparm - Johansson, Petter (SLU/Dept. of Forest Resource Management, 2007)
One of the most important components of a harvester is the crane. Most harvester cranes are only possible to pivot (or horizontally rotate) at the crane pillar. Cranab in Vindeln, Sweden, has developed a new type of harvester crane which has an extra pivot point on the outer boom. This makes it possible to reach around residual trees, easing thinning work in dense stands.